Primary care doctors’ understandings of and strategies to tackle health inequalities: a qualitative study - Exworthy, Mark (Prim Health Care Res Dev, 2019)
AIM: To examine general practitioners’ knowledge of and their role in tackling health inequalities, in relation to their professional responsibilities. BACKGROUND: Primary care is often seen as being in the frontline of addressing health inequalities and the social determinants of health (SDH). METHODS: A qualitative study with a maximum variety sample of English General Practitioners (GPs). In-depth, semi-structured interviews were held with 13 GPs in various geographical settings; they lasted between 30 and 70 min. Interviews were audio-recorded and transcribed. The analysis involved a constant comparison process undertaken by both authors to reveal key themes. FINDINGS: GPs’ understanding of health inequalities reflected numerous perspectives on the SDH and they employ various different strategies in tackling them. This study revealed that GPs’ strategies were changing the nature of (medical) professionalism in primary care. We locate these findings in relation to Gruen’s model of professional responsibility (comprising a distinction between obligation and aspiration, and between patient advocacy, community participation and political involvement). We conclude that these GPs do not exploit the full potential of their contribution to tackling health inequalities. These findings have implication for policy and practice in other practitioners and in other health systems, as they seek to tackle health inequalities.